The uniqueness of the experience of death in art video games - Strużyna, Hanna; Strużyna, Andrzej (Replay. The Polish Journal of Game Studies, 2015)
Video games present different meanings of death than those conditioned by social and cultural contexts. Most games treat the motif of death instrumentally. Therefore, death is usually a norm and a rule in typical video games. However, art games present a different sense of death, one that defies its conventional meanings. The article analyses the different presentations of death in three art games: "Passage" (Rohrer, 2007), "The Graveyard" (Tale of Tales, 2008) and "Queers in Love at the End of the World" (Anthropy, 2013). These productions prove that video games are an excellent medium to offer players a deep emotional experience, which can also encourage taking a fundamental and more profound reflection on the meaning of life and death.